Biology, cultivation and potential uses of passion fruit plant, passiflora species - Ramaiya, Shiamala Devi (2016)
Passiflora fruits are widely known for their unique flavour, fruity aroma, desirable organoleptic properties and essential nutrient contents. Passiflora plant is not native to Malaysia and it is cultivated in a small scale. The evolutions of cultivated Passiflora plants have also not been extensively investigated and there have been inconsistences in the identification suggesting more research needs to be conducted. Hence, the present research was carried out to examine the adaptability, biology and phenology of five Passiflora species, i.e., Passiflora edulis Sims (Purple), Passiflora edulis Sims (Frederick), Passiflora maliformis Linn., Passiflora quadrangularis Linn. and Passiflora incarnata Linn. The morphology and molecular characterization were also examined for the five species with additional accessions from other geographical locations (i.e., Passiflora edulis Sims (Pink), Passiflora edulis Sims (Yellow) and Passiflora foetida Linn. for species identification and confirmation. In addition the nutrition properties of the fruit juices were also evaluated. Apart from their juices, the plants’ agro by-products; leaves, stems and seeds were also examined for their utilization. All species have the ability adapt to the local condition with plants continuously grew and produced flowers and fruits all the year around. The flowering and fruiting were not synchronized and showed a marked phenological pattern with species. Different flowering peaks were observed, e.g., 4 peaks in P. edulis compared to a single peak in P. quadrangularis. This was followed by fruiting with two months after anthesis. Good fruit yields were observed throughout the year which was attributed to Passiflora species ability for self-pollination. The higher fruit yield was recorded in P. edulis (Purple) and P. quadrangularis compared to other species. In P. edulis (Purple), the annual fruit production were approximately, 119,174 fruits of 11,103.90 kg ha-1 with the weight ranged 56.4-156.5 g. The production of P. quadrangularis which produced bigger fruits, was 18,800.62 kg ha-1 (9585 fruits) with weight ranged 774.2-3034.4 g. The morphological study provided a useful tool for identification of Passiflora species. Using Principal Component Analysis (PCA) and Discriminant Analysis (DA) the morphological traits could be distinguished by the Passiflora species. Cluster analysis based on Spearman correlation coefficient further supported the species separation. Based on genetic characterization using nuclear ribosomal Internal Transcribed Spacer, ITS1-4 provided high resolution at species level and useful for differentiating the major groups of Passiflora subgenus. The phylogenetic relationships were consistent with results obtained for morphological assessments. The ITS also confirmed that the Passiflora accession from different geographical regions showed varied fruit colours (e.g., P. edulis produces purple, dark purple, pink red and yellow fruits) are actually genetically similar and belong to the same species of P. edulis. Ancillarily, Passiflora foetida which is placed in the Stipulata supersection evolved distantly from, P. Caerulea Linn. (same supersection), thus the placement of this species into a separate subgenus is supported by the present finding. Passiflora species mainly enters international trade in the form of fruit juice. Demands for the juice are increasing because of the juice’s exotic flavor and ample nutrient compositions. A cup of 247 mL Passiflora juices provided 6-21% of fiber, 3-7% of protein and ~34% of K, 60-80% Mg, >80% P and 90% Fe of daily recommended allowance of minerals. In addition, reducing sugars; glucose and fructose were the predominant sugar components. With respect to vitamin content, a serving of 247 mL Passiflora fruit juice offered 71 mg of vitamin C and 2000 I.U. of vitamin A, sufficient to fulfill the daily required amount. Passiflora juices also possessed higher total antioxidant activity (TAA), total phenolic content (TPC) and total flavonoid content (TFC). Passiflora plant parts, i.e., leaves, stems and seeds as agro by-products are sources of functional and bioactive compounds giving the plants value beyond that of their fruit juices. The leaves and stems possessed good antioxidant and antibacterial properties. The maximum antioxidant compound was from extracts of P. maliformis leaf and P. quadrangularis stem and correlated with their TAA and TPC. The gram-negative bacteria were generally less susceptible to Passiflora extracts than gram-positive bacteria. The seeds of Passiflora species were also rich in protein, dietary fiber with predominant insoluble dietary fiber (72%) and rich in oil with a yield of 24-30%. Based on the PCA, Passiflora seed oils possessed similar characteristics as sunflower and soybean oils. The cultivated five species of Passiflora plants have a good adaptation to the local climatic condition as evident by the plants’ growth, production of flowers and fruiting with good yield. Hence, the information gathered on the cultivation and management practices can be recommended to growers and farmers for large-scale cultivation. Furthermore, the ITS1-4 is useful in identifying genetically similar accessions. The finding revealed that, all above ground plant parts of Passiflora species can be utilized. The fruit juice is gaining visibility in drinks, food and health promoter and leaves, stems, and seeds could be utilized due to their nutritional and phytochemical attributes.